2008
DOI: 10.1262/jrd.19178
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Gap Junctions between Granulosa Cells and Oocytes in Ayu (Plecoglossus altivelis): Formation and Role during Luteinizing Hormone-dependent Acquisition of Oocyte Maturational Competence

Abstract: Abstract. Gap junctions (GJs) are intercellular channels. Molecules with a molecular weight of 1 kDa or less can pass back and forth between adjacent cells through GJs. Communication between oocytes and the somatic cells that surround them via GJs is known to play key roles to initiate oocyte maturation in many vertebrates. However, little is known of the detailed functions of ovarian GJs during oocyte maturation in fish. The oocyte maturation of fish is induced by a maturation-inducing steroid (MIS). The sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…During this process, the germinal vesicle migrates towards the oocyte periphery, the nuclear envelope breaks down, the first meiotic division occurs, and the chromosomes proceed to second meiotic metaphase where they arrest; at this point, the oocyte will ovulate and becomes an egg [ 51 ]. Oocyte maturation is also accompanied by important changes in the cytoarchitecture and function of the ovarian follicle, since steroidogenic pathways in granulosa cells are switched from estrogen to progestagen production, intercellular communication oocyte-granulosa cells is resumed, and the zona radiata becomes more compacted [ 39 , 52 , 53 ]. At this stage, ovarian transcripts associated with the regulation of intracellular signalling pathways (such as mapk13 in follicular cells, and ywhae ), and cystoskeleton ( mybph , gsna , myo10 , LOC100005008 ), as well as in the assembly of the nucleosome ( hist1h2be , myst3 ), were significantly regulated in Senegalese sole, which is consistent with the important nuclear and cytoplasmic changes occurring in the ovarian follicle during oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, the germinal vesicle migrates towards the oocyte periphery, the nuclear envelope breaks down, the first meiotic division occurs, and the chromosomes proceed to second meiotic metaphase where they arrest; at this point, the oocyte will ovulate and becomes an egg [ 51 ]. Oocyte maturation is also accompanied by important changes in the cytoarchitecture and function of the ovarian follicle, since steroidogenic pathways in granulosa cells are switched from estrogen to progestagen production, intercellular communication oocyte-granulosa cells is resumed, and the zona radiata becomes more compacted [ 39 , 52 , 53 ]. At this stage, ovarian transcripts associated with the regulation of intracellular signalling pathways (such as mapk13 in follicular cells, and ywhae ), and cystoskeleton ( mybph , gsna , myo10 , LOC100005008 ), as well as in the assembly of the nucleosome ( hist1h2be , myst3 ), were significantly regulated in Senegalese sole, which is consistent with the important nuclear and cytoplasmic changes occurring in the ovarian follicle during oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Both processes involve gonadotropins, and members of the Igf family. The increase in follicular gap junctions, composed of various forms of connexin proteins (York et al, 1993;Patiño and Kagawa, 1999;Bolamba et al, 2003), is a critical process in the acquisition of OMC (Yamamoto et al, 2008;Yamamoto and Yoshizaki, 2008;Yamamoto et al, 2011a). Both gonadotropins and Igf1 increase numbers of gap junctions (Yoshizaki et al, 1994;Chang et al, 1999Chang et al, , 2000Choi and Takashima, 2000;Choi and Takemura, 2001), and Lh, Fsh and Igf1 have connexin-specific and stage-specific effects on expression of connexins (Yamamoto et al, 2011a).…”
Section: F Transition From Vitellogenesis To Final Oocyte Maturationmentioning
confidence: 99%
“…Membrane progestin receptors (mPRs: Zhu et al, 2003 andreview: Thomas, 2012) mediate the stimulatory effects of MIS on resumption of meiosis (Thomas et al, 2004;Tokumoto et al, 2006Tokumoto et al, , 2007Tokumoto et al, , 2012Hanna et al, 2006;Zhu, 2009, 2011), and their expression is upregulated during OM (Zhu et al, 2003;Tokumoto et al, 2006, Hanna andZhu, 2009;Tubbs et al, 2010). OMC can be induced by gonadotropins (Patiño and Sullivan, 2002;Patiño et al, 2003;Weber et al, 2007;Yamamoto and Yoshizaki, 2008), and gonadotropin-induced upregulation of the mPR early in OM is strongly associated with increased OMC (review: Thomas, 2012).…”
Section: F Transition From Vitellogenesis To Final Oocyte Maturationmentioning
confidence: 99%
“…The temporal expression pattern and follicular localization of coho salmon cx43.2 showed a similar pattern to that of ayu cx34.9 [49]. In ayu, cx34.9 appears to contribute to formation of GJs between the oocyte and the granulosa cells, and may have an important role in transmitting the LH-signal received in the follicle cells to the oocyte via a second messenger such as cAMP during acquisition of OMC [14,15,49]. Although we have no empirical data on the function of coho salmon cx43.2 , it may have a similar role to ayu cx34.9 given the similarity of their spatiotemporal expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in ovarian GJs were also induced by insulin-like growth factor 1 (IGF1) treatment in red seabream [12]. Further, Yamamoto et al [14,15] found that culturing ovarian fragments with common GJ inhibitors prevented LH-induced acquisition of OMC in ayu, Plecoglossus altivelis , suggesting that ovarian GJ communication is essential for the LH-induced acquisition of OMC in this species. Thus, some ovarian GJs appear to be hormonally regulated and to have important roles during final maturation of the follicle in fishes.…”
Section: Introductionmentioning
confidence: 99%